Slr4, a newly identified S‐layer protein from marine Gammaproteobacteria, is a major biofilm matrix component. Issue 6 (15th September 2020) - Ali, Sura; Jenkins, Benjamin; Cheng, Jiujun; Lobb, Briallen; Wei, Xin; Egan, Suhelen; Charles, Trevor C.; McConkey, Brendan J.; Austin, John; Doxey, Andrew C.
Abstract: S‐layers are paracrystalline proteinaceous lattices that surround prokaryotic cells, forming a critical interface between the cells and their extracellular environment. Here, we report the discovery of a novel S‐layer protein present in the Gram‐negative marine organism, Pseudoalteromonas tunicata D2. An uncharacterized protein (EAR28894) was identified as the most abundant protein in planktonic cultures and biofilms. Bioinformatic methods predicted a beta‐helical structure for EAR28894 similar to the Caulobacter S‐layer protein, RsaA, despite sharing less than 20% sequence identity. Transmission electron microscopy revealed that purified EAR28894 protein assembled into paracrystalline sheets with a unique square lattice symmetry and a unit cell spacing of ~9.1 nm. An S‐layer was found surrounding the outer membrane in wild‐type cells and completely removed from cells in an EAR28894 deletion mutant. S‐layer material also appeared to be "shed" from wild‐type cells and was highly abundant in the extracellular matrix where it is associated with outer membrane vesicles and other matrix components. EAR28894 and its homologs form a new family of S‐layer proteins that are widely distributed in Gammaproteobacteria including species of Pseudoalteromonas and Vibrio, and found exclusively in marine metagenomes. We propose the name Slr4 for this novel protein family. Abstract : The S‐layer is the outermost protein layer surrounding bacterial cells. We discovered a new family of S‐layer proteins in marine bacteria that forms a paracrystalline square lattice surrounding cells. In addition, the S‐layer was found surrounding extracellular components in biofilms, suggesting that it may provide physical protection not only to cells but also to extracellular structures.